2022
DOI: 10.1016/j.ultsonch.2022.105932
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of acoustic cavitation threshold in water with non-condensable bubble nuclei

Abstract: Highlights A numerical model is presented for acoustic cavitation in water with non-condensable bubble nuclei. The phase change has a significant effect on bubble growth and collapse dynamics during acoustic cavitation. As the bubble nucleus size increases and the acoustic frequency increases, the cavitation threshold increases beyond the Blake threshold. The threshold predictions fitted as a function of bubble nucleus size and acoustic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…(14) are introduced to analyze the two-bubble motions in an ultrasonic field. Here, the maximum radii and of a single bubble are determined using the present numerical method or by solving the following Rayleigh-Plesset (RP) equation [6] . 4 …”
Section: Numerical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…(14) are introduced to analyze the two-bubble motions in an ultrasonic field. Here, the maximum radii and of a single bubble are determined using the present numerical method or by solving the following Rayleigh-Plesset (RP) equation [6] . 4 …”
Section: Numerical Analysismentioning
confidence: 99%
“… [2] , [3] . Fundamental studies have also been reported on ultrasound-driven droplet vaporization [4] , [5] , acoustic cavitation with non-condensable bubble nuclei [6] , and bubble oscillation on a rigid boundary [7] , [8] , [9] .…”
Section: Introductionmentioning
confidence: 99%
“…[26,27] Previous work involving the microbubbles contrast agents, [28,29] phase-shift perfluorooctyl bromide nanovesicles, [30] and perfluorohexane-encapsulated fullerene [31] into ultrasonic histotripsy has been proven to be an efficient method to increase cavitation nuclei and reduce cavitation threshold. [32][33][34][35] However, this method is still unsatisfactory since they allow cavitation for a very short time under pHIFU due to the rupture of their stabilizing gas shells. [36][37][38][39] Although gas-stable cavitation agents such as hollow mesoporous silica nanoparticles are stable, [40] they have a limited number of cavitation nuclei accommodated within hydrophobic pores.…”
Section: Doi: 101002/smll202302744mentioning
confidence: 99%
“…If an acoustic wave generates a sufficient negative pressure when propagating in a liquid, gas nuclei can grow into cavitation bubbles and experience expansion, compression, and even collapse [1] . Ultrasonic cavitation has widespread application in various fields.…”
Section: Introductionmentioning
confidence: 99%